Programas educacionais para a pequena infância na Itália - Tullia Musatti (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
Crèches in the north of Italy for children in the 0 3 year age bracket have been an international reference for teacher training in childrens education. Taking parents, children and teachers as actors, the article presents the crèches within the policies for childhood and emphasises the role of the family together with the State in the education of the young ones. It reflects upon Italian mothers, workers or not, and also on paternity/ maternity and the education of children at home and in the crèche. It describes two new types of programme for families and children concluding with the importance of offering the parents a wide range of choice for child care. These questions, which are part of the current debate in Italy on policy for childhood and the family, should also be part of research projects and innovative practices.